2004
DOI: 10.1016/j.femsle.2004.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferricin B inhibits bacterial macromolecular synthesis in and

Abstract: Most antimicrobial peptides have an amphipathic, cationic structure, and an effect on the cytoplasmic membrane of susceptible bacteria has been postulated as the main mode of action. Other mechanisms have been reported, including inhibition of cellular functions by binding to DNA, RNA and proteins, and the inhibition of DNA and/or protein synthesis. Lactoferricin B (Lfcin B), a cationic peptide derived from bovine lactoferrin, exerts slow inhibitory and bactericidal activity and does not lyse susceptible bacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 35 publications
2
40
1
Order By: Relevance
“…Although the cytoplasmic membrane of target cells (including that of bacteria) is widely believed to be the ultimate target of many AMPs, various intracellular potential targets have been proposed (26,61,62) to account for the ability of certain AMPs to spontaneously translocate across the plasma membrane of various cell types at nontoxic concentrations (63,64). Whether representing a final or intermediate step in the mechanism of action, it is nevertheless clear that the interaction of AMPs with the plasma membrane plays an important role in their biological activity.…”
Section: Nmr-calculated Secondary and Tertiary Structures And Electromentioning
confidence: 99%
“…Although the cytoplasmic membrane of target cells (including that of bacteria) is widely believed to be the ultimate target of many AMPs, various intracellular potential targets have been proposed (26,61,62) to account for the ability of certain AMPs to spontaneously translocate across the plasma membrane of various cell types at nontoxic concentrations (63,64). Whether representing a final or intermediate step in the mechanism of action, it is nevertheless clear that the interaction of AMPs with the plasma membrane plays an important role in their biological activity.…”
Section: Nmr-calculated Secondary and Tertiary Structures And Electromentioning
confidence: 99%
“…Interestingly, a Yersinia pestis homologue of this protein, Pla, is known to be expressed at body temperature and is a virulence factor involved in the mobility of the bacterium from a subcutaneous wound to distal sites [100]. Furthermore, studies that looked at the susceptibility of both Gram-positive and Gram-negative bacteria in the presence of protease inhibitors suggested that a number of intracellular proteases like DegP, also contributed to the intrinsic resistance of a number of bacteria to cationic peptides [101].…”
Section: Bacterial Resistance To Cationic Antimicrobial Peptidesmentioning
confidence: 99%
“…This innate immunity factor contains two antimicrobial domains: lactoferricin (LFC) 17-30, found as a pepsin digestion product [1,2], and lactoferrampin (LFA) 265-284 [3][4][5], which can also be released from bovine lactoferrin by proteolytic digestion. Related synthetic peptides from both domains show broad-spectrum bactericidal activities against a range of Gram-positive and Gram-negative bacteria [6][7][8][9]. In addition, LFC has been shown to have antifungal [10,11], antiviral [12][13][14][15], and antitumor activities [11,16].…”
Section: Introductionmentioning
confidence: 99%